OPERATION OF CYBER SECURITY IN TERTIARY INSTITUTION IN NIGERIA: PROBLEMS AND WAY FORWARD - Yunisa, Bintu; Abdullahi Jantullu , Safina; Ogochukwu Judith, Offia (Antis Publisher, 2025)
Objective: This study examines the challenges affecting the operation of cybersecurity systems in Nigerian tertiary institutions and proposes strategic solutions to enhance cybersecurity resilience in higher education. Method: This position paper is based on a comprehensive review of secondary data sourced from print and online publications, focusing on existing cybersecurity policies, infrastructure, and institutional frameworks. Results: The findings reveal critical challenges, including poor funding, inadequate cybersecurity infrastructure, weak cybercrime laws, lack of standardized national control, increasing cyber threats, shortage of cybersecurity professionals, decentralized network operations, rapid technological advancements, low awareness and training, and insufficient collaboration between institutions and government agencies. Novelty: This study highlights the urgent need for a structured national cybersecurity policy tailored for higher education institutions, emphasizing a multi-stakeholder approach involving government agencies, institutions, and cybersecurity professionals. The study recommends special funding allocations, enhanced infrastructure, regulatory policy frameworks, employment of cybersecurity experts, continuous professional training, and strengthened institutional-government collaboration to mitigate cybersecurity risks. The paper contributes to the ongoing discourse on cybersecurity in the education sector by advocating for an integrated, policy-driven approach to safeguarding digital assets in Nigerian tertiary institutions.